Delays in pulmonary decline in eteplirsen‐treated patients with Duchenne muscular dystrophy. Issue 3 (8th July 2022) - Iff, Joel; Gerrits, Charles; Zhong, Yi; Tuttle, Edward; Birk, Erica; Zheng, Yeya; Paul, Xander; Henricson, Erik K.; McDonald, Craig M.; ,
Abstract: Introduction/Aims: Pulmonary decline is a major issue in patients with Duchenne muscular dystrophy (DMD). Eteplirsen is a United States–approved treatment for patients with DMD and exon 51 skip‐amenable mutations. Previous analyses have shown that eteplirsen is associated with a statistically significant attenuation of pulmonary decline. In this study we evaluate the effect of eteplirsen treatment from newly available data sources on pulmonary function over time in patients with DMD. Methods: We used a post hoc pooled analysis to compare the percentage of predicted forced vital capacity (FVC%p) and projected time with pulmonary function milestones in patients with DMD and exon 51 skip‐amenable mutations receiving eteplirsen (Studies 204 and 301) or standard of care (SoC; Cooperative International Neuromuscular Research Group Duchenne Natural History Study). A mixed model for repeated‐measures framework was applied to evaluate the impact of eteplirsen. Results: An average annual rate of FVC%p decline for eteplirsen‐treated patients was estimated to be 3.47%, a statistically significant attenuation from the 5.95% rate of decline estimated in SoC patients ( P  = .0001). Using linear extrapolations of the model‐estimated decline in FVC%p, the attenuation in FVC%p decline for eteplirsen‐treated patients corresponded to a delay of 5.72 years in time to needing continuous ventilation, 3.31 years in time to needing nighttime ventilation, and 2.11 years in time to needing a cough assist device compared with SoC patients. Discussion: The attenuation of FVC%p decline suggests that eteplirsen‐treated patients had statistically significant and clinically meaningful attenuations in pulmonary decline compared with SoC patients.